Partition and Pluralism: Perceiving Epistemic Terrains of Hope and Resilience in Divided by Partition, United by Resilience – 21 Inspirational Stories from 1947 - Karmakar, Goutam; Pal, Payel (SARE: Southeast Asian Review of English, 2023)
Before India gained independence from Britain in 1947, when the partition was announced, the subcontinent instantly descended into riots, death, and destruction, culminating in one of the largest human waves of migration in history. Muslims in India were prompted to travel to Pakistan, while Hindus and Sikhs in Pakistan were urged to return home. Approximately 15 million people were displaced or forced to relocate, with between half a million and two million killed in the consequent violence. This post-partition history includes some courageous individuals who lost everything during partition but reconstructed their existences from the ground up and climbed to the leading positions in their respective disciplines. Divided by Partition, United by Resilience – 21 Inspirational Stories from 1947, edited by Mallika Ahluwalia and published in 2018 by Rupa Publications India, is one such book that chronicles the narratives of 21 Indians who endured the chaos and destruction of India’s Partition but managed to overcome their miseries to become living embodiments of accomplishment and excellence. Emphasising the stories’ affirmative ethos, which steps beyond the tropes of loss and precarity, this article analyses how these individuals established their agency and extraordinariness vis-à-vis various epistemic tools. The article puts forth that these stories can be read as representative testimonies of diversified trajectories in the epistemological field of the Partition literature and studies. This article focuses on unlearning the monolithic perceptions of 1947 and approaching them through the lens of epistemic pluralism. The article finally argues that there are other sides that go beyond the meta-significations of partition narratives, as demonstrated by individuals who, through their tireless efforts, drew new contours of self-assertion, thereby creating diverse and dynamic epistemologies. Keywords: Episteme, Partition, Resilience, Empowerment, Autonomy